Théories féministes de l'éducation : où est le care ? - Vanina Mozziconacci
In this article, I provide an overview of the field of U.S. feminist education in the 1980s-1990s in order to locate theories of care among the different models available. Using feminist theoretical typologies, I argue that care can be incorporated into two distinct - even opposite - models: critical pedagogy and ''feminine'' pedagogy. This ambiguity raises a number of questions about the theoretical status of care itself: should it be conceptualized as a model, as a category, or as a value for education?